How adult experience as a supervising decision-maker can inhibit learning: An examination of undergraduate senior projects. - Elliott Lauderdale (Adult Education Research Conference, 1997)
This paper reports on a preliminary investigation of a hypothesis generated from an ongoing examination of the senior research projects of a interdisciplinary adult degree program at an urban university. A review of adult education writing addressing the work of Chris Argyris reveals a tendency to overlook its application to this research problem. Does positive supervisory experience inhibit adult learning?